Pemetaan Potensi dan Komoditas Lokal Unggulan Perikanan Laut Kabupaten/Kota di Provinsi Nusa Tenggara Timur Tahun 2016 - Hudan Dhardiri; Susi Yulianti; Adilla Zikra (Jurusan Sosial Ekonomi Perikanan, 2022)
One of the government's development priorities in Nawa Cita to succeed the SDGs is to build economic independence by driving strategic sectors of the domestic economy, one of which is the marine fisheries sector. The region that has the potential to be developed, by utilizing the local potential of marine fisheries, is the Province of East Nusa Tenggara (NTT). NTT has a great marine fisheries potential because it has a sea area of approximately 200,000 km2 with a coastline of about 5,700 km2. The purpose of this study was to find out which districts/cities are classified as high potential in the marine capture fisheries sub-sector and what marine capture fisheries commodities have the highest potential in each of those districts/cities in NTT Province in 2016. The data used in this study were sourced from the Fisheries Service, NTT and the analytical method used is descriptive analysis, cluster analysis using the Fuzzy C-Medoids method, and Location Quotient. The results of the analysis show that there are 8 districts/cities classified as high potential in the marine capture fisheries sub-sector in NTT Province in 2016, which are East Sumba, Kupang, Alor, East Flores, Sikka, Ende, Manggarai, and Kupang City. The commodities that have the highest potential in the marine capture fisheries sub-sector in each of these potential areas are paperek fish, flying fish, kite, jackfruit seeds, selar, tembang, mackerel, and skipjack.